Factors Associated with Oral Discomfort at The Menopausal Stage: A Systematic Review - Yuli Fatzia Ossa; Yuniardini Septorini Wimardhani; Iwany Amaliah Badraduddin; Febriana Setiawati; Steffano Aditya Handoko; Lindawati Soetanto Kusdhany (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Menopause is a physiological process that all women experience and is often regarded as a sign of aging in women. The signs and symptoms of menopause are very diverse, and oral discomfort is one of the symptoms. Oral discomfort can interfere with oral cavity function, indirectly affecting nutrient intake. This study aims to evaluate factors associated with oral discomfort and oral manifestations of the menopausal stage. Review: This review is based on the PRISMA statement. A literature review incorporated observational studies from the last five years and across 5 databases.  An investigative question was formulated using the PEOS model, studies were selected, and a quality analysis was performed in accordance with the STROBE guidelines. The bibliometric analysis was performed, and the data were qualitatively analyzed. A total of 19 articles met the inclusion criteria, with the majority of oral manifestations at the menopausal stage being xerostomia, burning sensation, taste disturbances, and periodontitis. Duration of menopause, bad oral hygiene, lower salivary flow rate, higher calcium saliva concentration, and salivary estrogen level were found to be associated factors for oral discomfort at the menopausal stage. Conclusions: The menopausal stage may increase the risk of oral discomfort due to decreased estrogen levels in saliva. Since the estrogen receptor was found in the oral cavity, especially in the mucosa, salivary gland, and periodontium, it can directly affect the oral cavity.